Do the dental students have enough nutritional knowledge? A survey among students of a dental college in Telangana State - Yajesh Chalmuri; T Madhavi Padma; K. V. N. R. Pratap; P Vineela; L Surya Chandra Varma; Y Vidyasagar (Journal of Indian Association of Public Health Dentistry, 2018)
Introduction: Nutritional knowledge affects nutritional status and nutritional habits of individuals, families, and society. It is important to know the current level of nutritional knowledge among health-care professionals for successful health promotion. Aim: The aim of this study is to assess the nutritional knowledge among students of a dental college in Telangana state. Materials and Methods: A cross-sectional questionnaire study was conducted among dental students. A standard questionnaire which consisted of questions on awareness of current dietary recommendations, knowledge of food sources and nutrients, and on diet-disease relationships was administered to the students during college hours. The data collected was analyzed using descriptive statistics. Results: Among 400 dental students, majority of them were female (59.75%). The mean age of the participants was 22.29 ± 2.64 years. The nutritional knowledge on dietary recommendations was similar in both females (88.58%), and males (87.63%) which was not statistically significant (P = 0.5660) Postgraduates had more nutritional knowledge than undergraduates. Conclusion: It is learnt that males and females had similar nutritional knowledge; however, postgraduate students had more nutritional knowledge compared to undergraduates irrespective of the gender, and there is a need to improve the nutritional knowledge of undergraduate students.